We are free to change the world Hannah Arendt's lessons in love and disobedience - Stonebridge, Lyndsey 1965- (Jonathan Cape, 2024)
This bold new take on the life and ideas of political philosopher Hannah Arendt explores her lessons for living in an age of uncertainty'Exhilarating, brilliant and utterly original' PHILIPPE SANDS, author of East West Street'Beautifully written... Biography at its best'EDDIE GLAUDE, author of Begin AgainThe violent unease of today's world would have been all too familiar to Hannah Arendt. Tyranny, occupation, disenchantment, post-truth politics, conspiracy theories, racism, mass migration, the banality of evil: she had lived through them all.Born in the first decade of the last century, Arendt escaped fascist Europe to make a new life for herself in America, where she became one of the world's most influential - and controversial - public intellectuals. She wrote about power and terror, exile and love, and above all about freedom. Questioning - thinking - was her first defence against tyranny. In place of the forces of darkness and insanity, she pitched a politics of plurality, spontaneity and defiance. Loving the world, Arendt taught, meant finding the courage to protect it.Written with passion and authority, Lyndsey Stonebridge's We Are Free to Change the World illuminates Arendt's life and work and its urgent dialogue with our troubled present. It calls on each of us to think our way, as Hannah Arendt did - unflinchingly, lovingly and defiantly - through our own unpredictable times
Keywords: 20. Jahrhundert (1900 bis 1999 n. Chr.); BIOGRAPHY & AUTOBIOGRAPHY / Philosophers; Biografie: Philosophie und Sozialwissenschaften; Memoirs; PHI046000; PHILOSOPHY / Criticism; PHILOSOPHY / Political; POLITICAL SCIENCE / History & Theory; Politikwissenschaft; Social & political philosophy; Soziale und politische Philosophie; Deutschland; Vereinigte Staaten von Amerika, USA